22. BACTERIAL CHARACTERISTICS AND ANTIBIOTIC RESISTANCE OF GRAM-NEGATIVE BACTERIA CAUSING HOSPITAL ACQUIRED PNEUMONIA AT RESPIRATORY DEPARTMENT, THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: To determine the rate of pathogens and antibiotic resistance of gram-negative bacteria in hospital acquired pneumonia patients at the Respiratory Department, Thong Nhat hospital from April 2022 to April 2024.Methods: Prospective, descriptive.Results: Pathogens mainly gram-negative bacteria 83.6% (K. pneumoniae 28.4%; A. baumannii 19.4%; P. aeruginosa 17.9% and E. coli 10.4%); S. aureus 16.4%. All strains are resistant to cephalosporines and fluoroquinolones 60-100%. K. pneumoniae, P. aeruginosa and A. baumannii are resistant to 45-70% with imipenem and meropenem.Conclusion: The leading cause of hospital acquired pneumonia is gram negative bacteria. K. pneumoniae, P. aeruginosa and A. baumannii are highly resistant to carbapenems.
Keywords: Hospital-Acquired Pneumonia; antibiotic resistance